Survival Status and Predictors of Mortality Among Preterm Neonates Admitted to Mizan Tepi University Teaching Hospital, South West Ethiopia - Bereka B; Demeke T; Fenta B; Dagnaw Y (Dove Medical Press, 2021)
Bayisa Bereka,1 Tigist Demeke,1 Belete Fenta,2 Yalemtsehay Dagnaw3 1School of Nursing, Jimma University, Jimma, Oromia Regional State, Ethiopia; 2School of Midwifery, Jimma University, Jimma, Oromia Regional State, Ethiopia; 3Department of Nursing, Mizan Tepi University, Mizan Tepi, South Nations, Nationalities and People Region, EthiopiaCorrespondence: Bayisa Bereka Email baayisaab@gmail.com; bayisakiso@yahoo.comObjective: The main objective of this study was to assess survival status and predictors of mortality among preterm neonates admitted to Mizan Tepi University Teaching Hospital.Materials and Methods: A retrospective cohort study was conducted on 568 randomly selected neonates. All preterm neonates admitted in NICU from May 9, 2016 to December 30, 2019 were the source population. Data were extracted from medical chart and entered to EpiData version 4.4.2.1 and analyzed by STATA version 14. Descriptive statistics, bivariate and multivariable analyses were done in a Cox regression model. Variables with P-value of < 0.05 were considered statistically significant in predicting the preterm mortality.Results: Out of 568 preterm neonates, 199 (35%) died with an incidence rate of 62.15 (54.09- 71.41) deaths per 1000 person-day-observations with median survival time of 15 days. Vaginal mode of delivery (adjusted hazard ratio, AHR: 1.78, 95%CI: 1.05- 3.08), non-cephalic presentation (AHR:1.8, 95%CI: 1.04- 3.06), born from mothers with no ANC follow-up (AHR: 1.9, 95%CI: 1.29- 3.01), fifth minute APGAR score < 7 (AHR: 1.87, 95%CI: 1.31- 2.68), RDS (AHR: 1.74, 95%CI: 1.28- 2.36), did not receive KMC (AHR: 1.45, (95%CI: 1.06- 1.98), did not cry immediately after birth (AHR: 2.81, 95%CI: 2.03- 3.93)), VLBW (AHR: 2.67, 95%CI: 1.29- 5.53), low birth weight (AHR: 2.24, 95%CI: 1.15- 4.39), and hypothermia (AHR: 1.36, 95%CI: 1- 1.84) were significantly associated with preterm mortality.Conclusion: Preterm neonatal mortality was high and the predictors were almost all preventable and treatable. Therefore, emphasis should be given toward prevention and early anticipation, and management of these predictors.Keywords: censored, mortality, preterm neonate, predictors, survival